Establishment of topographic circuit zones in the cerebellum of scrambler mutant mice - Reeber, Stacey L.; Loeschel, Courtney A.; Franklin, Amanda; Sillitoe, Roy V. (Frontiers in Neural Circuits, 2013)
The cerebellum is organized into zonal circuits that are thought to regulate ongoing motor behavior. Recent studies suggest that neuronal birthdates, gene expression patterning, and apoptosis control zone formation. Importantly, developing Purkinje cell zones are thought to provide the framework upon which afferent circuitry is organized. Yet, it is not clear whether altering the final placement of Purkinje cells affects the assembly of circuits into topographic zones. To gain insight into this problem, we examined zonal connectivity in scrambler mice; spontaneous mutants that have severe Purkinje cell ectopia due to the loss of reelin-disabled1 signaling. We used immunohistochemistry and neural tracing to determine whether displacement of Purkinje cell zones into ectopic positions triggers defects in zonal connectivity within sensory-motor circuits. Despite the abnormal placement of more than 95% of Purkinje cells in scrambler mice, the complementary relationship between molecularly distinct Purkinje cell zones is maintained, and consequently, afferents are targeted into topographic circuits. These data suggest that although loss of disabled1 distorts the Purkinje cell map, its absence does not obstruct the formation of zonal circuits. These findings support the hypothesis that Purkinje cell zones play an essential role in establishing afferent topography.